2023
DOI: 10.1002/eji.202250247
|View full text |Cite
|
Sign up to set email alerts
|

Bystander activation of Bordetella pertussis‐induced nasal tissue‐resident memory CD4 T cells confers heterologous immunity to Klebsiella pneumoniae

Abstract: Tissue‐resident memory CD4 T (TRM) cells induced by infection with Bordetella pertussis persist in respiratory tissues and confer long‐term protective immunity against reinfection. However, it is not clear how they are maintained in respiratory tissues. Here, we demonstrate that B. pertussis‐specific CD4 TRM cells produce IL‐17A in response to in vitro stimulation with LPS or heat‐killed Klebsiella pneumoniae (HKKP) in the presence of dendritic cells. Furthermore, IL‐17A‐secreting CD4 TRM cells expand in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Since CD8 + CD103 + T RM cells do not show an increase in TCR signaling activity and seem to respond in a TCR‐independent manner after antigen reencounter, it will be interesting to determine what signals activate these cells. A recent report found that CD4 + T RM cells in the lung that formed after Bordetella pertussis infection in mice were able to respond to non‐cognate immune challenges 97,98 . These findings show that the TCR‐independent activation of T RM can occur in both CD4 + and CD8 + T RM cells and suggest that T RM might acquire innate‐like features to respond to secondary infection at barrier sites.…”
Section: Trm In Secondary Infectionsmentioning
confidence: 79%
See 1 more Smart Citation
“…Since CD8 + CD103 + T RM cells do not show an increase in TCR signaling activity and seem to respond in a TCR‐independent manner after antigen reencounter, it will be interesting to determine what signals activate these cells. A recent report found that CD4 + T RM cells in the lung that formed after Bordetella pertussis infection in mice were able to respond to non‐cognate immune challenges 97,98 . These findings show that the TCR‐independent activation of T RM can occur in both CD4 + and CD8 + T RM cells and suggest that T RM might acquire innate‐like features to respond to secondary infection at barrier sites.…”
Section: Trm In Secondary Infectionsmentioning
confidence: 79%
“…A recent report found that CD4 + T RM cells in the lung that formed after Bordetella pertussis infection in mice were able to respond to non-cognate immune challenges. 97,98 These findings show that the TCR-independent activation of T RM can occur in both CD4 + and CD8 + T RM cells and suggest that T RM might acquire innatelike features to respond to secondary infection at barrier sites. The lack of proliferative capacity of CD103 + T RM cells might be a physiological adaptation to limit immunopathology.…”
Section: T R M In S Econdary Infec Ti On Smentioning
confidence: 79%
“…These data indicate that interactions between CD4 T cells and APCs at this time shape the subsequent memory pool. Lung airway epithelial cells are some of the first cells to be infected with IAV 43 and by positioning themselves near airways, memory CD4 T cells have the potential to respond rapidly following a re-infection, either in an antigen-specific manner via presentation by an APC, including epithelial cells 44, 45 , or potentially, in response to local cytokines 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the production of IL-17 not only appeared to be involved in the generation of lung T RM cells but also played a critical role in T RM cell-mediated protection against infection, especially CD4 + T RM cells. For example, CD4 + IL-17 + T RM cells have been demonstrated to be critical for the clearance of B. pertussis [ 57 , 58 ], pneumonic Yersinia pestis infection [ 42 ], Mycobacterium tuberculosis [ 59 ] and Klebsiella pneumonia [ 52 ]. Similar results were also observed in CD8 + T RM cells, which showed that the CD8 + T RM cells in patients with erosive oral lichen planus displayed enhanced cytokine production, including IFN-gamma, TNF-a and IL-17 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%